Generalisability of clinical registers used for drug safety and comparative effectiveness research: coverage of the Swedish Biologics Register. Issue 3 (15th November 2010) - Neovius, M; Simard, JF; Sundström, A; Jacobsson, L; Geborek, P; Saxne, T; Feltelius, N; Klareskog, L; Askling, J
Abstract : Objective: To determine coverage and generalisability of data in the Swedish Biologics Register ARTIS. Methods: Patients with adult onset rheumatoid arthritis (RA) were identified in the National Patient Register and the Swedish Rheumatology Quality Register, including the ARTIS cohort of patients exposed to biological agents. Exposure to etanercept and adalimumab between 2006 and 2008 was determined by register linkage to the Prescribed Drug Register which contains patient-level data on >99% of all etanercept and adalimumab use in Sweden. Results: Of 62 897 patients with RA, 6510 had received treatment with etanercept or adalimumab according to the Prescribed Drug Register. Of these, 5673 were also registered in ARTIS, resulting in a national coverage of 87%. The regional variation was small with >85% coverage in 18 of 21 counties. In multivariable analysis, ARTIS-registered and non-registered patients did not differ by age (p=0.62), sex (p=0.84) or education level (p=0.24). Conclusion: Nationwide drug dispensing and demographic data may function as quality metrics for coverage and generalisability assessments. Using such data, the coverage of ARTIS was estimated at 87% with no indications of compromised external generalisability regarding demography.